1985
DOI: 10.2307/3899409
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Forage Intake by Range Ruminants: A Review

Abstract: Variation in voluntary forage intake is undoubtedly the major dietary factor determining level and efficiency of ruminant production. This variation is largest and least predictable for grazing ruminants. Range ruminant productivity and efficiency is relatively low due, in part, to intake limitations; therefore, productivity could probably be increased most by increasing intake. Most available literature points to digestibility and rate of ingesta passage and reticula-rumen fill as primary mechanisms of intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
1
6

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(111 citation statements)
references
References 83 publications
(63 reference statements)
4
100
1
6
Order By: Relevance
“…Probably, the level of addition of lipid used was not high enough to limit intake, because this reduction is usually a consequence of reduction of food passage rate through the rumen, a variable that was not affected by the addition of lipid either (P = 0.498). The reduction of ruminal digestibility of fiber can also reduce intake, especially of aNDFom whenever fill is the limiting factor (Conrad et al, 1964;Ellis, 1978;Allison, 1985;Allen, 1996). In this study, as previously shown, a reduction of MRRT was not observed with the addition of lipid; however, the digestibility of fiber was reduced by the addition of lipid, but the reduced digestibility did not affect the aNDFom intake.…”
Section: Table 3 -P-values Of the Model Effects As Latin Square (Ls)supporting
confidence: 70%
“…Probably, the level of addition of lipid used was not high enough to limit intake, because this reduction is usually a consequence of reduction of food passage rate through the rumen, a variable that was not affected by the addition of lipid either (P = 0.498). The reduction of ruminal digestibility of fiber can also reduce intake, especially of aNDFom whenever fill is the limiting factor (Conrad et al, 1964;Ellis, 1978;Allison, 1985;Allen, 1996). In this study, as previously shown, a reduction of MRRT was not observed with the addition of lipid; however, the digestibility of fiber was reduced by the addition of lipid, but the reduced digestibility did not affect the aNDFom intake.…”
Section: Table 3 -P-values Of the Model Effects As Latin Square (Ls)supporting
confidence: 70%
“…The same stocking rate may result in different grazing pressure because of differences in grassland condition, cow behavior and physiology, and micro-distribution of resources in a pasture (Allison 1985). Utilization was quantified using ocular estimation in 0.5 m 2 (1 m 3 0.5 m) areas at 36 uniformly spaced subplots in each of the 16 pastures (for a total of 576 subplots; Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Intake of poorly digestible, low-energy diets is thought to be controlled mostly by physical factors such as ruminal fill and digesta passage, whereas consumption of highly digestible, high-energy diets is controlled by the energy demands of the animal and metabolic factors (NRC, 1987). Allison (1985) cited evidence indicating voluntary intake of forage diets is limited by reticulorumen capacity and rate of digesta disappearance from the reticulorumen. When offered poorquality forages, cattle eat to a constant ruminal fill.…”
Section: Resultsmentioning
confidence: 99%
“…Given the imThe Professional Animal Scientist 28 ( 2012 ):664-669 TECHNI CAl NOTE: Estimating beef-cattle forage demand: Evaluating the animal unit concept portance of properly balancing animal demand with forage supply and the discrepancy among AU definitions, it is imperative to know which factors need to be accounted for when defining an AU. Allison (1985) listed body size, physiological status, body condition, supplementation, forage preference, forage availability, and grazing systems as factors affecting forage intake. It was hypothesized both BW and physiological status would affect DMI; therefore, the objective of this experiment was to evaluate the effect of BW and physiological state on forage intake and compare it to standard AU intake values.…”
Section: Introductionmentioning
confidence: 99%